Agreement between a new swept-source ocular coherence tomography and a Placido disc-dual Scheimpflug ocular biometric devices. Issue 2 (March 2023) - McLintock, Cameron; Niyazmand, Hamed; Seo, Shiney; Barrett, Graham; Kumar Nilagiri, Vinay; Karimian, Sahar; McKelvie, James
Purpose: To evaluate the agreement between two biometry devices, the Heidelberg Anterion and the Galilei G6 Lens Professional. Methods: Eyes were scanned with both biometry devices. Analysis of inter-device agreement was conducted for the following metrics: flat (K1), steep (K2) and mean K (Km) for anterior, posterior and total cornea, lens thickness (LT), central corneal thickness (CCT), anterior chamber depth (ACD), white to white (WTW) and axial length (AL). Generalised Estimating Equations were used to account for inter-eye correlation. Bland-Altman analysis was conducted to derive the mean difference (MD) and limits of agreement (LoA) between devices. Differences were deemed clinically significant if they would result in a change in post-operative refraction of 0.25D or more. Results: 159 eyes of 91 patients were included. For the anterior cornea, no significant MD was found for K1 (−0.11D) and K2 (−0.10D), although a significant MD was found for Km (−0.10D). For posterior cornea, while there were no significant MDs between devices, the LoAs were wide for both posterior K1(−0.70, 0.68) and posterior K2 (−1.01, 1.29). For total corneal power, significant MDs were found in K1 (0.36D), and Km (0.26D) but not for K2 (0.17D). Significant MDs were found for LT (0.179mm), CCT (−0.005mm), ACD (−0.111mm) and WTW (−0.158mm), but not for AL (−0.021mm, p > 0.05). Conclusion: There are statistically but not clinically significant differences between Anterion and Galilei G6 Lens Professional in anterior Km, LT, CCT, ACD and WTW. Measurements of the posterior and total cornea are not interchangeable between devices.